Efficiency of Village Regulations in Indonesia: Efisiensi Peraturan Desa Di Indonesia - Firda Nur Hizrah; Viona Adira Kosuma (Universitas Muhammadiyah Sidoarjo, 2026)
Background: Village regulations constitute a fundamental legal instrument in Indonesia’s regional autonomy framework, positioning villages as the lowest yet autonomous level of governance. Specific background: The enactment of Law Number 6 of 2014 on Villages provides a legal basis for villages to formulate regulations reflecting community aspirations, democratic values, and local wisdom. Knowledge gap: Despite this framework, the efficiency of village regulations remains constrained by regulatory inconsistency, political dynamics, and limited institutional capacity at the village level. Aims: This study examines the efficiency of village regulations through the construction of legal politics based on philosophical, juridical, and sociological foundations. Results: The findings indicate that regulatory alignment across levels of government and village institutional capacity play a central role in shaping regulatory efficiency. Novelty: This research positions village regulation efficiency as a product of legal–political construction rather than administrative compliance. Implications: Strengthening participatory mechanisms and harmonizing legal frameworks are essential to support efficient village governance and sustainable local development in Indonesia. Highlights Village regulations operate within legal and political constraints. Regulatory alignment supports efficient village governance. Institutional capacity shapes regulatory implementation at village level. Keywords Village Regulations, Legal Politics, Regional Autonomy, Local Governance, Participatory Governance